2020
DOI: 10.1002/jemt.23586
|View full text |Cite
|
Sign up to set email alerts
|

Marginal adaptation and fracture strength of endocrowns manufactured with different restorative materials: SEM and mechanical evaluation

Abstract: Endocrowns were manufactured using different restorative materials to evaluate the marginal adaptation and fracture strength. Fifty endodontically treated mandibular first molar teeth were divided into five groups (n = 10). Endocrowns were obtained from lithium disilicate glass ceramic ingots by heat‐press technique (Group e.max Press: GEP), and from feldspathic blocks (Group Cerec: GC), polymer infiltrated ceramic network blocks (Group Enamic: GE), lithium disilicate glass ceramic blocks (Group e.max CAD: GEC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 28 publications
1
24
0
1
Order By: Relevance
“…Given this, alternative materials with a more compliant behavior have been introduced for endocrown fabrication, such as resin composites and polymer-infiltrated ceramics. They exhibit higher resilience and more resistance to higher occlusal forces [ 20 , 21 ]. Recently, a modified polyetheretherketone (PEEK) material, with favorable biocompatibility and good adhesion properties to tooth structures, also become a viable option for endocrowns [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given this, alternative materials with a more compliant behavior have been introduced for endocrown fabrication, such as resin composites and polymer-infiltrated ceramics. They exhibit higher resilience and more resistance to higher occlusal forces [ 20 , 21 ]. Recently, a modified polyetheretherketone (PEEK) material, with favorable biocompatibility and good adhesion properties to tooth structures, also become a viable option for endocrowns [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…1,3-5,11-56 Of those, 45 were selected based on title, abstracts, and full-text analysis. 1,[3][4][5][37][38][39][40][41][42][43][44][45][46][47][48][49][52][53][54] Of the 45 full-text studies, 27 were excluded based on abstract evaluation, 4,5,11,13,15,16,18,19,21,23,26,28,30,33,[38][39][40][41][43][44][45][46]48,49,[52][53][54] and 18 were completely reviewed. 1,3,12,14,17,20,22,24,…”
Section: Results Study Selectionmentioning
confidence: 99%
“…An electronic search was conducted on Medline/Pubmed and identified 50 relevant studies. 1,3-5,11-56 Of those, 45 were selected based on title, abstracts, and full-text analysis. 1,3-5,11…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only four papers focused on the differences between a classical full crown and endocrown. [19][20][21]. Also there is other study shown the marginal adaptation of CAD/CAM endocrown had superior marginal seating than a classical full crowns [22].…”
Section: Discussionmentioning
confidence: 99%